Upaya Mempertahankan Bangunan Heritage di Kawasan Kampung Peneleh Kota Surabaya Sebagai Identitas Kawasan - Wahyu Purnomo Putri, Adinda Najma Rosyadah; Elviana , Eva (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The city of Surabaya is a city with long historical value. Even today, many heritage areas are still maintained with the aim of preserving culture, one of which is Kampung Peneleh which has many heritage buildings. Heritage buildings are buildings with historical value inherited from the past. The existing buildings form an identity as the historic area of ​​ Kampung Peneleh, the identity of the area in question is a form of characteristic of an area. Kampung Peneleh has been designated as a historical area based on the Decree of the Mayor of Surabaya number 188.45/004/402.1.04/1998.  This research aims to determine the efforts of the people of Kampung Peneleh to maintain their historical values. This research uses an observation method by observing how the people of Kampung Peneleh are able to maintain their historical value and analyzing the buildings in Kampung Peneleh so that they can determine the identity of the area. The results obtained from this research are the identification of heritage buildings in Kampung Peneleh and the efforts of the local community and government to maintain the identity of the Kampung Peneleh area.